أثر استخدام الذكاء الاصطناعي في تحسين إدارة المشاريع الهندسية (Comprehensive Journal of Science, 2026)
Engineering project management is undergoing radical changes as a result of the digital revolution, with artificial intelligence (AI) emerging as a critical tool for increasing operational efficiency, reducing errors, and enhancing the quality of planning and execution. This research aims to examine the direct impact of AI technology on engineering project management, specifically forecasting accuracy, resource efficiency, and increased communication between technical teams.The study results showed that AI has significantly improved schedule planning, reduced human errors, and improved overall project performance. Participants also emphasized the need to enhance team collaboration and adhere to budgets and timelines. However, the research found that one of the most significant obstacles is the lack of qualified personnel to operate these devices.The study recommended several measures, including increased investment in digital infrastructure, intensified engineer training programs, the development of policies that encourage technological innovation, the provision of accurate data, and the development of legislative frameworks that regulate the safe and responsible use of AI.These findings indicate that AI is not merely a complement, but rather an imperative for improving the quality and efficiency of engineering projects and keeping pace with the demands of the digital age.
Keywords: Artificial Intelligence, Engineering Project Management, Smart Planning, Data Analysis.